Estimation of skin permeation by liquid chromatography - Sara Soriano-Meseguer; Elisabet Fuguet; Adriana Port; Martí Rosés (International Association of Physical Chemists (IAPC), 2018)
Dermal absorption is a key process in the drug delivery studies of the pharmaceutical and cosmetic industries, as well as in the fields of dermal toxicology, risk assessment, and the exposure of environmental pollutants. This process is typically described by the skin-water permeability coefficient. However, in vivo determination is laborious and expensive. Thus, in the last few years, the development of prediction models from structure descriptors or subrogation through physico-chemical measurements has gained interest. In the present work, a previous subrogation model based on the chromatographic retention on a common C18 column has been tested for a wide set of drugs with very different chemical nature and having a wide range of permeability values. A total of 65 compounds have been used to establish the correlation between skin permeation and the HPLC retention, corrected by the McGowan volume of the drug. Afterwards it was successfully validated in terms of robustness and prediction ability. Finally, the permeability coefficient was estimated for a set of 29 new drugs, and results compared to the ones obtained by other estimation methods, as well as the available in vitro measured values, with very good agreement.